Efficacy of Bilateral Transversus Abdominis Plane and Ilioinguinal-Iliohypogastric Nerve Blocks for Postcaesarean Delivery Pain Relief under Spinal Anesthesia - Seid Adem Ahemed; Zewditu Abdissa Denu; Habtamu Getinet Kassahun; Demeke Yilikal Fentie (Anesthesiology Research and Practice)
Background. Caesarean delivery can be associated with considerable postoperative pain. While the benefits of transversus abdominis plane (TAP) and ilioinguinal-iliohypogastric (II-IH) nerve blocks on pain after caesarean delivery via Pfannenstiel incision have been demonstrated, no enough investigations on the comparison of these blocks on pain after caesarean delivery have been conducted in our setup. Method. An institutional-based prospective observational cohort study was conducted to compare the analgesic efficacy of those blocks. We observed 102 postoperative parturients. The outcome measure was the severity of pain measured using a numeric rating scale. Result. Twenty-four hours after surgery, the NRS score at rest was (0.90 ± 0.80) versus (0.67 ± 0.58) and at movement (1.2 ± 1.07) versus (0.88 ± 0.76) for the TAP and II-IH groups, respectively. Twenty-four hours after surgery, the mean tramadol consumption was (55.45 ± 30.51) versus (37.27 ± 27.09) mg in TAP and II-IH groups, respectively (p = 0.009). The mean first analgesic requirement time was also prolonged in the II-IH group. Conclusion and Recommendations. There was no statically significant difference between TAP and II-IH blocks regarding postoperative pain score, but the II-IH block significantly reduced the total tramadol consumption and prolonged the time to first analgesic request than TAP. Thus, we recommend the II-IH nerve block.